LITERASI KEUANGAN SYARIAH BAGI GURU DAN SISWA MADRASAH ALIYAH MUHAMMADIYAH - wahyi busyro; Rika Septianingsih; abu nawas; mohd ario wahdi elsye (Jurnal Pengabdian UntukMu NegeRI, 2018)
Muhammadiyah University of Riau is one of universities in Riau and every college must do catur dharma which is the vision of all universities in Indonesia. One of the forms of catur dharma college is to carry out community service. Community service is an activity of academic community that utilizes science and technology to advance people's prosperity and educate the life of the nation. The form of community service undertaken by Sharia Banking Lecturers is holding a seminar with the theme “Financial Literacy For Teacher and Student of Madrasah Aliyah Muhammadiyah". After the holding of this seminar is expected teachers and students can manage finances well and in accordance with Islamic Shari'a and can be a person who berkemudian in the future.